Thatcherism in the 21st Century
XIII, 296 p. 2 illus.
Keywords: This collection examines the social and cultural legacy of Thatcherism in the 21st century. Drawing upon perspectives from a range of disciplines, it considers how Thatcherism manifests itself today and how we can assess its long-term impact. The book is divided into four sections, which offer different ways of conceptualising and addressing questions of legacy: the ideological impact of Thatcherism on the Conservative Party and on the country; the long-term impact of Thatcherism across different parts of the UK; how Thatcherism has altered social attitudes to everything from welfare spending to Europe; and how popular historical accounts of Thatcherism have become embedded in different parts of contemporary British culture. The essays in this volume draw upon newly available archival materials, oral histories, social attitudes surveys and parliamentary debates to provide a well-rounded perspective on Thatcherism today. Antony Mullen is the director of the Thatcher Network, UK. Stephen Farrall is a research professor at the University of Derby, UK. David Jeffery is a lecturer at the University of Liverpool, UK.